Establishing an Anti-Müllerian hormone cutoff for diagnosis of polycystic ovarian syndrome in women of reproductive age-bearing Indian ethnicity using the automated Anti-Müllerian hormone assay - Nalini Mahajan; Jasneet Kaur (Wolters Kluwer Medknow Publications, 2019)
Context: Polycystic ovary syndrome diagnosed by Rotterdam criteria, is the most common cause of anovulatory infertility. The criteria of polycystic ovarian morphology (PCOM) are subject to operator variability and technological advances. Serum anti-Müllerian hormone (AMH) level has been proposed as a more reliable alternative to antral follicle count. There is a paucity of data on use of AMH for diagnosis of PCOS in Indian women. Aim and Objectives: The aim of this study is to determine a cutoff level for AMH that could facilitate diagnosis of PCOS and its phenotypes in women of Indian origin using the automated (Roche) assay and to compare the competence of oocytes in PCOS and non-PCOS women undergoing in vitro fertilization-intracytoplasmic sperm injection (IVF-ICSI). Materials and Methodology: A total of 367 women undergoing treatment at our fertility center between February 2017 and August 2017 were prospectively enrolled in this study. Of these, 133 were diagnosed with PCOS, 69 had isolated PCOM, and 165 (controls) had normal ovaries on ultrasound examination. Serum AMH levels were assessed using the fully automated Roche Elecsys® immunoassay. Gonadotropin-releasing hormone antagonist protocol was used for IVF-ICSI in all patients. Statistical Analysis Used: Quantitative variables were compared using the Mann-Whitney test. Qualitative variables were correlated using the Chi-square test. P < 0.05 was considered to be statistically significant. Results: Mean AMH concentrations in women with PCOS was higher (7.56 ± 4.36 ng/mL) in comparison to PCOM and controls. Serum AMH concentration >5.03 ng/mL could facilitate diagnosis of PCOS (area under the curve = 0.826); sensitivity -70.68%, specificity of 79.91%. There was no difference in the ratio of mature to total oocytes retrieved in the three groups (P > 0.05). Mean number of mature oocytes was lower in controls than PCOS and PCOM (P < 0.001). Conclusions: Serum AMH concentration >5.03 ng/mL could be used as cutoff value for the diagnosis of PCOS in women of Indian origin.